The Investigation of the Influence of a Local Elastic Nonlinearity on Vibrations of Plane Truss Members - Pielorz, A. (Engineering Transactions, 2003)
The paper concerns theoretical investigations of plane trusses subject to longitudinal de-formations, using nonlinear discrete-continuous models. An external excitation is applied to a rigid body located in a truss joint. In this joint a visco-elastic discrete element with a spring having a nonlinear symmetric stiffness is also located. It is assumed that the spring characteristic is of a soft type. Four nonlinear functions describing this characteristic are proposed. In the considerations the wave method is applied similarly to the case of a hard characteristic in [1]. The numerical analysis focus on the investigation of the effect of the local nonlinearity with a soft characteristic for two examples of plane trusses.